All you need - Hensley, Sam; Ser, Rnady; Mike Gabrawy (Plattsburgh, New York Direct Source Special Products, 2001)
Kellie Martin, stars in this intense family drama about a woman who struggles to put her life in order, even while her family spirals out of control. Faced with a disintegrating marriage, an alcoholic mother and an emotionally detached father attempts to take charge of her own life, and help her family through a major crisis.
Director of Photography, Jim Orr ; Production Designer, Erik Olson ; Editor, Kim Rettberg ; Casting, Elisabeth Jereski ; Co-producer, Kim Papazian ; Executive producer, Randy Holleschau.
Kellie Martin, Janet Carroll, Robert Pine.
In English.
Keywords: Romance drama; Feature films